Hydroxyapatite For Poly(α-Hydroxy Esters) Biocomposites Applications. (3rd April 2019) - Ng, Hon-Meng; Bee, Soo-Tueen; Tin Sin, Lee; Ratnam, Chantara T.; Rahmat, Abdul Razak
Abstract: This article focuses on providing a systematic review on various fundamental properties of composite based on poly(α-hydroxy esters) and hydroxyapatite (HAp) for application in bone tissue engineering. Poly(α-hydroxy esters), a well-known synthetic biopolymer has attracted considerable interest to be employed for synthesis of bone graft substitute material with HAp mainly due to its bioresorbability, variable biodegradation rate and melt-processibility. Such features are simultaneously attractive for both biomedical application and industrial-scale productions. Besides the main function of hydroxyapatite as bioactive ceramic filler in composite to induce new bone formation upon polymer bioresorption, HAp can also serve as reinforcement for matrix polymer by providing sufficient mechanical support for cell attachment. Moreover, HAp plays a significant role in determining other composite properties, such as resistance to ingress of body fluid, body temperature ageing, relaxation movement of polymer segment, and in vivo biodegradation. These properties constitute as the fundamental requirements in field of bone tissue regeneration which is desirable to be achieved by unique composite system based on poly(α-hydroxyesters) and HAp particles.